Engineering Sphingobium sp. to Accumulate Various Carotenoids Using Agro-Industrial Byproducts - Liu, Mengmeng; Yang, Yang; Li, Li; Ma, Yan; Huang, Junchao; Ye, Jingrun (Frontiers in Bioengineering and Biotechnology, 2021)
Carotenoids represent the most abundant lipid-soluble phytochemicals that have been shown to exhibit benefits for nutrition and health. The production of natural carotenoids is not yet cost-effective to compete with chemically synthetic ones. Therefore, the demand for natural carotenoids and improved efficiency of carotenoids biosynthesis has driven the investigation of metabolic engineering of native carotenoids producers. In this study, a newly Sphingobium sp. was isolated and found it could use variety of agro-industrial by-products like soybean meal, okara and corn steep liquor to accumulate large amounts of nostoxanthin. Then we tailored it into three mutated strains that instead specifically accumulated ~5 mg/g CDW of phytoene, lycopene, zeaxanthin due to the loss-of-function of the specific enzyme. A high-efficiency targeted engineering carotenoid synthesis platform was constructed in E. coli for identifying the functional roles of candidate genes of carotenoids biosynthetic pathway in Sphingobium sp.. For further prolong metabolic pathway, we engineered Sphingobium sp. to produced high-titer astaxanthin (10 mg/g DCW) through balance the key enzymes β-carotene ketolase (BKT) and β-carotene hydroxylase (CHY). Our study provided more biosynthesis components for bioengineering of carotenoids and highlights the potential of the industrially important bacterium for production of various natural carotenoids.